Langkah-Langkah Pengembangan Eksistensi Model Kurikulum Pendidikan Anak Usia Dini - Ernawati (Journal of Gemilang, 2024)
The PAUD curriculum is a set of plans about early childhood learning objectives that range between the ages of 0 to 6 years that intend to optimally develop the potential of children. Lack of teacher attention and lack of facilities and infrastructure trigger the development of children's potential that is less than optimal. The objectives of this study are to: 1) describe the form of PAUD curriculum development model, and 2) describe the implementation of PAUD curriculum model. This research uses a literature study method that relies on bibliographic sources from books and articles in scientific journals related to the subject matter. The results of this study show that: 1) the ECD curriculum development model can be changed by adding, reducing and improving the curriculum periodically, and 2) the ECD curriculum models include: a) High/Scope curriculum, b) Creative curriculum, c) Vygotsky curriculum, and d) Waldorf curriculum.